Comparative yield and nutritive value of forages from two cereal - legume based cropping systems. 1. Crop yields and the nutritive value of forages - Crosse, S.; Umunna, N.N.; Osuji, P.O.; Khalili, H.; Tegegne, Azage; Tedla, A. (1998)
The effects of two cropping systems (1 and 2) on grain and fodder yields and nutritive quality of the fodder were studied in a randomized complete block desgin experiment over a period of two cropping years. Crops and crop combinations in system 1 were oat-vetch, wheat-trifolium, teff straw, and cowpea, System 2 was similar to system 1 except that maize-lablab replaced wheat-trifolium. Neither grain yields nor yields of straws or hays were affected by intercropping. Grain and straw yields were about 25 percent higher than yields reported for smallholder systems. Using the standard measures of quality such as crude protein, neutral-detergent fibre, and acid-detergent lignin, the presence of legumes in crop mixtures improved forage quality resulting in higher degradation characteristics than would be expected from cereals alone.